2017
DOI: 10.17492/vision.v3i2.7899
|View full text |Cite
|
Sign up to set email alerts
|

Goods And Services Tax (GST): A Comprehensive and Uniform Indirect Tax Reform in India

Abstract: Overcoming the loopholes in the existing indirect tax regime, Goods and services tax (GST) is a major indirect tax reform in India. India is very close to its implementation, tentatively from 1 July 2017 as announced by Sri Arun Jaitely, the current Finance Minister. Goods and services tax (GST) is a nationwide tax levied on supply of goods and services in India. It is a destination based value added tax levied at each stage in supply chain right from the manufacturer to the consumer with benefit of input tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Theoretically, income determines a citizen's budget constraint, which could affect whether to pay the e‐levy. We expect that those who earn more income will be willing to pay the e‐levy compared to those with lower incomes (Gupta, 2016; McGee, 2011). Thus, income can exert either a positive or negative effect on levy tax payments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, income determines a citizen's budget constraint, which could affect whether to pay the e‐levy. We expect that those who earn more income will be willing to pay the e‐levy compared to those with lower incomes (Gupta, 2016; McGee, 2011). Thus, income can exert either a positive or negative effect on levy tax payments.…”
Section: Methodsmentioning
confidence: 99%
“…In general, those with greater earnings are often more inclined to pay taxes than those with lower income. For instance, Gupta (2016) used the contingency valuation method to examine consumers' willingness to pay taxes to reduce carbon dioxide emissions from the passenger transportation sector on roads. Using a sample of 321 respondents, the study found that income had a positive and significant impact on willingness to pay a carbon tax.…”
Section: Literaturementioning
confidence: 99%
“…The problem of evasion could also be a serious concern for developing countries like Ethiopia; as economic development is usually significantly hampered by poor tax revenues because of the matter of evasion. (9) (10) Ethiopia has a rock bottom tax to GDP ratio (10.7%) far below the typical for Sub Saharan African and low-income countries generally, and evasion contributes tons to this poor performance. (11) (12) An empirical study of evasion as a positive connection between tax rates and evasion.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Proper planning, administration, timely guidance to the industry and training to both the tax officers and payers on GST will aid its smooth implementation. Gupta (2016) investigated about the principal theoretical issues involved in financial relations between different layers of the government in a federal set up. It looks at the distribution of taxation powers between the Centre and state governments.…”
Section: Review Of Literaturementioning
confidence: 99%